PUBLIC PERCEPTION AND WILLINGNESS TO PAY FOR URBAN VEGETATION RESTORATION AND MANAGEMENT IN ABEOKUTA, OGUN STATE - Shittu, A. M.; Kehinde, M. O.; Dare, A. M. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
The study assesses perception and willingness to pay (WTP) for urban vegetation restoration and management in Ibara housing estate and its surrounding areas in Abeokuta, Ogun State. A total number of 120 respondents were selected through a systematic random sampling technique. Descriptive statistics was used to describe the socio-economic characteristics of the respondents; WTP was assessed by contingent valuation method while influence of various factors on the urban dwellers’ WTP was analysed within the framework of a generalised Double Hurdle model that nest the Tobit. Mean WTP for the management plan of the urban vegetation restoration is ₦375.83. Perception results showed that majority (94.0%) of the respondents- perceived trees to provide shades while about 59.2% and 44.0% perceived as herbs and means of reducing pollution. Regression results revealed that the likelihood of supporting urban vegetation restoration was higher among female-headed households but declined with household size. WTP rose with income, declined with increase in formal education and in early years, but rose significantly in later years. Similarly, WTP was significantly lower among traders than civil servants but was significantly higher among people in profession practice & services. This study, therefore concludes that participation and willingness to pay for urban vegetation restoration and management in the study area were influenced by various socio-economics factors.